Strategi Pemenangan Jokowi dan Ma’ruf Amin dalam Pemilihan Presiden 2019 melalui Pencitraan Politik - Tasya Maurhena Pusparimba; Yusa Djuyandi; Ratnia Solihah (PERSPEKTIF, 2021)
This study aims to see the winning strategy of the candidate pairs for Jokowi and Ma'ruf Amin in the 2019 presidential election, especially in terms of political imagery. Using Newman and Shet's theory by looking at reinforcement strategies, rationalization strategies, inducement strategies, and confrontation strategies. The method used is descriptive qualitative research methods through in-depth interviews and literature review. Primary data was obtained through interviews with resource persons, namely the success team and volunteer team for the Indonesia Maju coalition, secondary data consisting of books and related documents. The results showed that the candidate pairs Jokowi and Ma'ruf Amin tried to carry out various strategic tactics in order to present themselves as candidates who had a populist image, were liked, were honest and had a dominant ideology of democratic-socialism.